Discovering computers fundamentals your interactive guide to the digital world - Shelly, Gary B.; Vermaat, Misty (Shelly Cashman series, 2012)
Provides students with an introduction to computers. This text offers a solution to successfully teach students the relevancy of computer concepts in their personal, professional and academic lives through various exercises that focus on problem solving and critical thinking